Energy security in Kazakhstan: The consumers' perspective. (August 2021) - Mouraviev, Nikolai
Abstract: This paper aims to investigate the consumers' perceptions and opinions regarding various threats, impediments, and opportunities present in Kazakhstan when it considers its energy security. The chosen theoretical framework allows consumers' views to be explored through the lens of three variations of the energy security concept: as an arrangement ensuring availability, accessibility, affordability, and acceptability of resources; as security of energy supply; and as conceptualisation that focuses on ever-increasing utilisation of renewables and a corresponding decrease in reliance on fossil fuels. Using a qualitative approach based on in-depth interviews, this study identifies the consumers' views on three themes including security of energy supply, the role of renewables in ensuring energy security, and the links between energy security and environmental sustainability. The findings show that the views of the majority of study participants on energy security can be distilled into the opinion that oil is a guarantor of the nation's independence and stability. Study participants do not see how energy security links to economic restructuring. As for the role of renewables in strengthening energy security, residents of rural areas are likely to contribute to renewable energy generation. Interviewees viewed the role of renewables in ensuring ecological sustainability as very insignificant. Highlights: Consumers' perceptions of energy security in Kazakhstan have been investigated. Interviewees perceive oil as a guarantor of the nation's independence and stability. Study participants do not link energy security to restructuring of the economy. Policy has to encourage residents of rural areas to generate energy from renewables. Policy needs to enhance the role of renewables in ensuring ecological sustainability.